1995
DOI: 10.1111/j.1600-0447.1995.tb09567.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for post‐stroke depression

Abstract: An unselected cohort of 285 stroke patients, median age 69 years, were studied for correlation between potential risk factors and the 1-year incidence of post-stroke depression (PSD). The following factors correlated significantly with PSD: a history of previous stroke, a history of previous depression, female gender, living alone and social distress prestroke. Further, social inactivity, decrease in social activity, pathological crying and intellectual impairment at 1 month but not functional outcome correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
163
4
25

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(212 citation statements)
references
References 30 publications
20
163
4
25
Order By: Relevance
“…The present study demonstrated that high neuroticism conferred a 3-to 5-fold greater risk of post-stroke depression. A past history of depression has been shown previously to be a risk factor for post-stroke depression (Andersen et al, 1995). The current study found that a past history of depression, anxiety, or "nerves" conferred at least an eight-fold risk of post-stroke depression, consistent with other research (Ng et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study demonstrated that high neuroticism conferred a 3-to 5-fold greater risk of post-stroke depression. A past history of depression has been shown previously to be a risk factor for post-stroke depression (Andersen et al, 1995). The current study found that a past history of depression, anxiety, or "nerves" conferred at least an eight-fold risk of post-stroke depression, consistent with other research (Ng et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
“…In recent years a number of studies have examined the aetiology, clinical course and treatment of post-stroke depression (Gall, 2001). The evidence from these studies suggests that post-stroke depression is a heterogeneous group of disorders of multifactorial aetiology and differing clinical presentations (Andersen et al, 1995;Burvill et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Shimoda and Robinson 46 suggested that impairments such as social isolation or visual perceptual disorders associated with right hemisphere strokes may play a role in the etiology of depression in the chronic phases of stroke. Andersen et al 22 suggested that this trend may be reflective of the neuropsychological changes that may follow hemisphere strokes: catastrophic reaction with left hemisphere strokes and denial and/or neglect or aprosody with right hemisphere lesions. Accordingly, several follow-up studies have suggested that PSD occurring in the chronic phase may have a different mechanism than acute or subacute PSD.…”
Section: Timing Of First Interview After Strokementioning
confidence: 99%
“…Patients were selected from 2 main sources: hospital-based patients † or community-based patients. 22,23,29,34,35,42,47 The population base of the study sample has been proposed by some investigators 15,48 to influence the outcome of the association between lesion location and PSD. When studies are examined according to population source, 2 trends emerged ( Figure 2).…”
Section: Source Populations and Study Samplesmentioning
confidence: 99%
See 1 more Smart Citation